The Effect of Financial Literacy on Financial Well-Being of Lecturers Mediated by The Financial Behavior (Pusat Riset dan Inovasi Nasional, 2026)
Financial wellness is an essential indicator of an individual’s standard of living, including that of lecturers. In Indonesia, lecturer welfare often receives limited attention, despite its direct impact on education quality and student learning outcomes. Lecturer welfare is influenced not only by income level but also by the ability to manage that income effectively. As educators, lecturers are expected to strengthen their understanding of financial management. A solid grasp of financial concepts supported by sound economic behavior is anticipated to enhance lecturers’ awareness and understanding of financial management, ultimately improving their financial well-being. However, despite their high educational background, many lecturers still face challenges in managing their finances. Insufficient financial knowledge often leads to poor financial decisions, which negatively affect their overall financial health. This study aims to analyze the effect of financial literacy (FL) on the financial well-being (FWB) of lecturers at Maranatha Christian University, with financial behavior (FB) functioning as a mediating variable. The research employs a quantitative method using an explanatory approach. Data were collected through a Google Form questionnaire and analyzed using structural equation modeling (SEM) with AMOS software. The sample consisted of lecturers from various study programs selected through stratified random sampling. The findings indicate that FL does not directly influence FWB; instead, FL positively affects FB. The results further show that FB has a positive impact on FWB, confirming FB as a mediator linking FL and FWB. Thus, financial literacy must be translated into proper financial behavior to achieve financial well-being.